Free Voluntary Reading to Promote Learners Autonomy in Vocabulary Acquisition: The Case of Universitas Internasional Batam - Arapa Efendi; Christine Deyani (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Purpose - The purpose of this study was to find out what strategies EFL students used to developvocabulary through personalized reading materials. In addition, this study was also conducted to findout how Free Voluntary Reading help students develop their vocabulary as EFL. Design/methodology/approach - This study uses a descriptive qualitative research design in answeringthe research questions. Researchers conducted in-depth interviews to the students of EFL class of 2019and 2020 in the English Language Education Department. There were 11 students (22,4%) who wereinterviewed in this research. Findings/results – The results showed that the strategies used by EFL students were as follows: readingauthentic materials, choosing reading materials according to genres, making notes about newvocabulary, and always looking for any content with English subtitles. In addition, the researcher alsofound out how several forms of Free Voluntary Reading helped the vocabulary development of EFLstudents. Originality/value - Free Voluntary Reading has an important influence on EFL students, especially indeveloping vocabulary. Paper type – Research paper